Diseño interior 3D del laboratorio multimedia audiovisual, mediante el uso de herramientas de modelado, de la carrera de diseño gráfico de la Universidad Técnica de Cotopaxi, período 2013 - Caiza Chicaiza, Saúl Wilfrido (2015)
The objective of this work was to develop a proposal for 3D interior design of the Multimedia and Audiovisual Laboratory by using modeling tolls as a guide to identify the different spaces and multimedia equipment in which the students from the Graphic Design School in the Technical University of Cotopaxi spend time. The methodology for developing the 3D Interior Desing Laboratory is a set of techniques and tools such as surveys and interviews which helped obtaining the data necessary for executing the Project. This implementation and adaptation is shown by a virtual tour which grafically describes the real locations and spaces available to the users.